Knowledge and Practice of Internship Students on the Emergency Crash Cart System in a Selected Tertiary Care Hospital, Mangaluru, Karnataka, India - Nair, Varsha B.; Joseph, Shilpa; Thomas, Shintu; Sharvana, Sharvana; PK, Pranav; Mathew, Shycil (Journal of Health and Allied Sciences NU, 2022)
Introduction A crash cart is the trolley for storing lifesaving equipment and drugs in a hospital. During an emergency situation, nurses are left with confusion and hurry in getting the emergency medication and equipment. Typically, the crash cart system remains locked until a code blue triage is initiated by the hospital. This lack of exposure leads to poor competency and confident in performing essential tasks during a code blue. A well-organized crash cart system can save a lot of time and confusion during an emergency, which in turn can save a life.Aim The aim of this study was to identify the knowledge and practice of internship students on emergency crash cart system and to find the correlation between knowledge and practices of nursing internship students on maintenance of emergency crash cart system.Materials and Methods A descriptive correlative research study was conducted among 93 nursing internship students tertiary care hospital, Mangaluru, Karnataka, India. The samples were selected by using purposive sampling techniques. Demographic proforma, structured knowledge questionnaire on knowledge regarding emergency crash cart system with 32 items was used to determine the level of knowledge and observation practice checklist with 24 items was used to assess the practice of internship students on maintenances of emergency crash cart system. Descriptive and inferential statistics was used to analyze the collected data.Results Majority (89; 95.7%) of the internship students are in the age group of 20 to 25 years and most (59; 63.4%) of internship students are working in wards. Of that 79 (84.9%) internship students have average knowledge with mean 18.1, median 19, and standard deviation (SD) 3.2. Majority 90 (96.7%) of the internship students have satisfactory practice on emergency crash carts with mean 22.9, median 23, and SD 1. 11. There is a moderate positive linear relationship between knowledge and practice scores of the internship students on the emergency crash cart system (r = 0.38, df =92, p= 0.05).Conclusions The study concludes nursing internship students have average knowledge about emergency crash cart system. And the practice of internship students on maintenance of crash cart was satisfactory. The study thus implies the need for frequent reinforcement and training programs, which may help the internship students to improve knowledge on emergency crash cart systems. There should be clear instructions about the arrangement and use of a crash cart in each and every unit.
Keywords: code blue; crash cart system; practices; nursing internship students